1985
DOI: 10.1016/0014-5793(85)80382-3
|View full text |Cite
|
Sign up to set email alerts
|

N‐terminal amino acid sequence and some properties of isopenicillin‐N synthetase from Cephalosporium acremonium

Abstract: Isopenicillin-N synthetase (IPNS) was purified to homogeneity from Cephalosporium acremonium C0728. The enzyme existed in two states during purification; an oxidised state with a disulphide linkage and its reduced state. These two forms can he interconverted in the presence or absence of thiol agents, and separated by fast protein liquid chromatography (FPLC) with the strong anion exchange Mono-Q column. The enzyme is a monomer with a molecular mass of 38 kDa and ~15.05. The first 50 amino acid N-terminal sequ… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
7
0

Year Published

1987
1987
2004
2004

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 30 publications
(8 citation statements)
references
References 7 publications
1
7
0
Order By: Relevance
“…It appears to be a monomer polypeptide since the SDS-denatured form of the enzyme showed the same relative molecular weight as the nondenatured form. Similar conclusions have been obtained with the IPN synthase of P. chrysogenum (24) and A. chrysogenum (2). The molecular weight of the acyltransferase (30,000) was slightly lower than that of the IPN synthase of P. chrysogenum (Mr, 39,000) (24) and A. chrysogenum (Mr, 38,416) (28).…”
Section: Discussionsupporting
confidence: 79%
“…It appears to be a monomer polypeptide since the SDS-denatured form of the enzyme showed the same relative molecular weight as the nondenatured form. Similar conclusions have been obtained with the IPN synthase of P. chrysogenum (24) and A. chrysogenum (2). The molecular weight of the acyltransferase (30,000) was slightly lower than that of the IPN synthase of P. chrysogenum (Mr, 39,000) (24) and A. chrysogenum (Mr, 38,416) (28).…”
Section: Discussionsupporting
confidence: 79%
“…It was shown that P. chrysogenum IPNS is strongly inhibited by glutathione and is also sensitive to cobalt inhibition (267). IPNS was purified to homogeneity from A. chrysogenum (27,142,251) and has subsequently been obtained from P. chrysogenum (267), A. nidulans (339), several actinomycetes such as S. clavuligerus (153), and the gram-negative bacterium Flavobacterium sp. (250).…”
Section: Structural Genes and Deduced Proteinsmentioning
confidence: 99%
“…(250). It was shown that two interconvertable forms of the enzyme exist, an oxidized state with a disulfide linkage and a reduced state (27).…”
Section: Structural Genes and Deduced Proteinsmentioning
confidence: 99%
“…Although the reactions catalysing the biosynthesis of penicillins and cephalosporins have been demonstrated in cell-free systems, it is only very recently that we have begun to understand the mechanisms of some of these reactions. The enzyme catalysing the cyclization of the tripeptide L-a-aminoadipoyl-L-cysteinyl-D-valine to form isopenicillin N (isopenicillin N synthetase) has been purified to homogeneity from Cephalosporium acremonium (Acremonium chrysogenum) (Pang et al, 1984;Hollander et al, 1984;Baldwin et al, 1985) and this enzyme cloned into Escherichia coli (Samson et al, 1985).…”
Section: Introductionmentioning
confidence: 99%